2019
DOI: 10.1111/jbi.13669
|View full text |Cite
|
Sign up to set email alerts
|

Forest community assembly is driven by different strata‐dependent mechanisms along an elevational gradient

Abstract: Aim The mechanisms driving forest community assembly along elevational gradients remain elusive. The distinct strata in heterogeneous forest are subject to differing assembly mechanisms. This study aims to evaluate how different ecological mechanisms driving forest community assembly across strata and spatial scales, and to identify how these assemblages respond to different abiotic or biotic variables along an elevational gradient. Location Yulong Mountain within Hengduan Mountains, Southwest China. Taxon See… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 71 publications
2
43
1
Order By: Relevance
“…Therefore, greater microsite availability at the larger spatial scale (100 m 2 ) led to the presence of plant species with different trait values and consequently higher trait divergence. With respect to the dependence of community assembly on spatial scale, our results are not in agreement with previous studies which showed that contrasting assembly mechanisms are responsible for different trait diversity patterns along a gradient of spatial scale [27,30,32,33,43].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Therefore, greater microsite availability at the larger spatial scale (100 m 2 ) led to the presence of plant species with different trait values and consequently higher trait divergence. With respect to the dependence of community assembly on spatial scale, our results are not in agreement with previous studies which showed that contrasting assembly mechanisms are responsible for different trait diversity patterns along a gradient of spatial scale [27,30,32,33,43].…”
Section: Discussioncontrasting
confidence: 99%
“…For example, trait divergence in more stressful abiotic conditions can be attributed to facilitation [25]. Another notation is that trait convergence in more favorable environments has been found to be related to the exclusion of weak competitors [24,27,30]. In contrast to the described niche-based assembly processes, the assemblages might also result from stochastic processes (neutral theory) [28,31].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations